Behavior of SnO2 in the tin-bearing iron concentrate during a reduction sintering process - Su, Zijian; Zhang, Yuanbo; Liu, Bingbing; Chen, Jun; Li, Guanghui; Jiang, Tao (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
The reserve of tin-bearing iron ores is very large in China. However, they have not been utilized sufficiently so far due to the complex embedded relationship between iron- and tin-bearing minerals. In the present work, the behavior of tin in the tin-bearing iron concentrates during a reduction sintering process (RSP) were studied using XRD, SEM-EDS, chemical valence state analysis and morphology analysis. The results show that there is about 30 mass% tin deprived from the tin-bearing iron concentrates by the RSP. The tin-bearing phases remained in the finished sinters exist as the form of stannic (Sn4+), stannous (Sn2+) compound and metallic Sn (Sn0). The atmosphere in the sinter bed during the RSP is theoretically suitable for the volatilization of SnO(g). However, the gas composition and temperature of the sintering gas flow are changeable, which bring about adverse effect to the deprivation of tin. It seems that the RSP is a feasible route to utilize the tin-bearing iron concentrates. However, the tin content in the sinter mixture should be controlled below 0.12 mass% for the purpose of preparing qualified sinters by the RSP.